1. Question:যোগ নির্ণয় কর: ৩.ক. `(a - b)/a + (a + b)/b` খ. `a/(bc) + b/(ca) + c/(ab)` গ. `(x - y)/x + (y - z)/y + (z - x)/z` ঘ. `(x + y)/(x - y) + (x - y)/(x + y)` 

    Answer
    ক. `(a - b)/a + (a + b)/b`
    
             `= (b(a - b) + a(a + b))/(ab)`
    
            `= (ab - b^2 + a^2 + ab)/(ab)`
    
            `= (a^2 + 2ab - b^2)/(ab)`
    
        উত্তর: `(a^2 + 2ab - b^2)/(ab)`
    
    
    
       খ. `a/(bc) + b/(ca) + c/(ab)`
    
              `= (a^2 + b^2 + c^2)/(abc)`
    
        উত্তর: `= (a^2 + b^2 + c^2)/(abc)`
    
       গ. `(x - y)/x + (y - z)/y + (z - x)/z`
    
               `= (yz(x - y) + zx(y - z) + xy(z - x))/(xyz)`
    
               `= (xyz - y^2z + xyz - z^2x + xyz - x^2y)/(xyz)`
    
               `= (3xyz - x^2y - y^2z - z^2x)/(xyz)`
    
       উত্তর:  `= (3xyz - x^2y - y^2z - z^2x)/(xyz)`
    
       ঘ.  `(x + y)/(x - y) + (x - y)/(x + y)`
    
             `= ((x + y)^2 + (x - y)^2)/((x - y)(x + y))`
    
            `= (x^2 + 2xy + y^2 + x^2 - 2xy + y^2)/((x + y)(x - y))`
    
             `= (2x^2 + 2y^2)/(x^2 - y^2)`
    
             `= (2(x^2 + y^2))/(x^2 - y^2)`
    
       উত্তর: `= (2(x^2 + y^2))/(x^2 - y^2)`






    1. Report
  2. Question:যোগ নির্ণয় কর: ৩.ঙ.`1/(x^2 - 3x + 2) + 1/(x^2 - 4x + 3) + 1/(x^2 - 5x + 4)` 

    Answer
    `1/(x^2 - 3x + 2) + 1/(x^2 - 4x + 3) + 1/(x^2 - 5x + 4)`
    
     `= 1/(x^2 - 2x - x + 2) + 1/(x^2 - 3x - x + 3) + 1/(x^2 - 4x - x + 4)`
    
     `= 1/(x(x - 2) - 1(x - 2)) + 1/(x(x - 3) - 1(x - 3)) `
    
                                     `+ 1/(x(x - 4) - 1(x - 4))`
    
     `= 1/((x - 2)(x - 1)) + 1/((x - 3)(x - 1)) + 1/((x - 4)(x - 1))`
    
     `= ((x - 3)(x - 4) + (x - 2)(x - 4) + (x - 2)(x - 3))/((x - 1)(x - 2)(x - 3)(x - 4))`
    
     `= (x^2 - 7x + 12 + x^2 - 6x + 8 + x^2 - 5x + 6)/((x - 1)(x - 2)(x - 3)(x - 4))`
    
      উত্তর: `= (3x^2 - 18x + 26)/((x - 1)(x - 2)(x - 3)(x - 4))`






    1. Report
  3. Question:যোগ নির্ণয় কর: ৩.চ. `1/(a^2 - b^2) + 1/(a^2 + ab + b^2) + 1/(a^2 - ab + b^2)` 

    Answer
    `1/(a^2 - b^2) + 1/(a^2 + ab + b^2) + 1/(a^2 - ab + b^2)`
    
      `= 1/(a^2 - b^2) + (a^2 - ab + b^2 + a^2 + ab + b^2)/((a^2 + ab + b^2)(a^2 - ab + b^2)`
    
      `= 1/(a^2 - b^2) + (2a^2 + 2b^2)/((a^2 + b^2 + ab)(a^2 + b^2 - ab))`
    
      ` = 1/(a^2 - b^2) + (2a^2 + 2b^2)/((a^2 + b^2)^2 - (ab)^2)`
    
      ` = 1/(a^2 - b^2) + (2a^2 + 2b^2)/(a^4 + 2a^2b^2 + b^4 - a^2b^2)`
    
       `= 1/(a^2 - b^2) + (2a^2 + 2b^2)/(a^4 + a^2b^2 + b^4)`
    
       `= (a^4 + a^2b^2 + b^4 + 2(a^2 + b^2)(a^2 - b^2))/((a^2 - b^2)(a^4 + a^2b^2 + b^4))`
    
        `= (a^4 + a^2b^2 + b^4 + 2(a^4 - b^4))/((a^2 - b^2)(a^4 + a^2b^2 + b^4))`
    
        `= (a^4 + a^2b^2 + b^4 + 2a^4 - 2b^4)/((a^2 - b^2) {(a^2)^2 + a^2b^2 + (b^2)^2})`
    
       `= (3a^4 + a^2b^2 - b^4)/((a^2)^3 - (b^2)^3)`
    
       `= (3a^4 + a^2b^2 - b^4)/(a^6 - b^6)`
    
       উত্তর: `(3a^4 + a^2b^2 - b^4)/(a^6 - b^6)`






    1. Report
  4. Question:যোগ নির্ণয় কর: ৩.ছ. `1/(x - 2) + 1/(x + 2) + 4/(x^2 - 4)` জ.` 1/(x^2 - 1) + 1/(x^4 - 1) + 4/(x^8 - 1)` 

    Answer
    ছ.`1/(x - 2) + 1/(x + 2) + 4/(x^2 - 4)`
    
      `= (1(x + 2) + 1(x - 2))/((x - 2)(x + 2)) + 4/(x^2 - 4)`
    
      `= (x + 2 + x - 2)/((x - 2)(x + 2)) + 4/(x^2 - 4)`
    
      `= (2x)/(x^2 - 4) + 4/(x^2 - 4)`
    
      `= (2x + 4)/(x^2 - 4)`
    
      `= (2(x + 2))/((x - 2)(x + 2))`
    
      `= 2/(x - 2)`
    
      উত্তর:  `= 2/(x - 2)`
    
    
     জ. ` 1/(x^2 - 1) + 1/(x^4 - 1) + 4/(x^8 - 1)`
    
          `= 1/(x^2 - 1) + 1/(x^2 - 1)(x^2 + 1)) + 4/(x^8 - 1)`
    
          `= (x^2 + 1 + 1)/((x^2 - 1)(x^2 + 1)) + 4/(x^8 - 1)`
    
         `= (x^2 + 2)/(x^4 - 1) + 4/((x^4 + 1)(x^4 - 1))`
    
         `= ((x^2 + 2)(x^4 + 1) + 4)/((x^4 + 1)(x^4 - 1))`
    
         `= (x^6 + x^2 + 2x^4 + 2 + 4)/((x^4)^2 - 1^2)`
    
         `= (x^6 + 2x^4 + x^2 + 6)/(x^8 - 1)`
    
        উত্তর:  `= (x^6 + 2x^4 + x^2 + 6)/(x^8 - 1)`






    1. Report
  5. Question:বিয়োগফল নির্ণয় কর: ক. `a/(x - 3) - a^2/(x^2 - 9)` খ. `1/(y(x - y)) - 1/(x(x + y))` গ. `(x + 1)/(1 + x + x^2) - (x - 1)/(1 - x + x^2)` ঘ. `(a^2 + 16b^2)/(a^2 - 16b^2) - (a - 4b)/(a + 4b)` ঙ. `1/(x - y) - (x^2 - xy + y^2)/(x^3 + y^3)` 

    Answer
    ক. `a/(x - 3) - a^2/(x^2 - 9)`
    
         `= a/(x - 3) - a^2/(x^2 - 3^2)`
    
         `= a/(x - 3) - a^2/((x + 3)(x - 3))`
    
        ` = (a(x + 3) - a^2)/((x - 3)(x + 3))`
    
        ` = (ax + 3a - a^2)/((x - 3)(x + 3))`
    
         `= (ax + 3a - a^2)/(x^2 - 9)`
    
     উত্তর: `= (ax + 3a - a^2)/(x^2 - 9)`
    
    
      খ. `1/(y(x - y)) - 1/(x(x + y))`
    
         `= (x(x + y) - y(x - y))/(xy(x - y)(x + y))`
    
         `= (x^2 + xy - xy + y^2)/(xy(x - y)(x + y))`
    
         `= (x^2 + y^2)/(xy(x - y)(x + y))`
    
         `= (x^2 + y^2)/(xy(x^2 - y^2)`
    
          উত্তর: `= (x^2 + y^2)/(xy(x^2 - y^2)`
    
     গ. `(x + 1)/(1 + x + x^2) - (x - 1)/(1 - x + x^2)`
    
      `= ((x + 1)(1 - x + x^2) - (x - 1)(1 + x + x^2))/((1 + x + x^2) (1 - x + x^2))`
    
      `= ((x - x^2 + x^3 + 1 - x + x^2) - (x + x^2 + x^3 - 1 - x - x^2))/((1 + x^2 + x) (1 + x^2 - x))`
    
     `= ((x^3 + 1) - (x^3 - 1))/((1 + x^2)^2 - x^2)`
    
     `= ((x^3 + 1) - (x^3 - 1))/(1 + 2x^2 + x^4 - x^2)`
    
    ` = (x^3 + 1 - x^3 + 1)/(x^4 + x^2 + 1)`
    
     `= 2/(x^4 + x^2 + 1)`
    
       উত্তর :` 2/(x^4 + x^2 + 1)`
    
    
     ঘ.  `(a^2 + 16b^2)/(a^2 - 16b^2) - (a - 4b)/(a + 4b)`
    
     `= (a^2 + 16b^2)/(a^2 - 16b^2) - (a - 4b)/(a + 4b)`
    
     `= (a^2 + 16b^2)/((a + 4b) (a - 4b)) - (a - 4b)/(a + 4b)`
    
     `= (a^2 + 16b^2 - (a - 4b)^2)/((a + 4b) (a - 4b))`
    
     `= (a^2 + 16b^2 - (a^2 - 2.a.4b + 16b^2))/((a + 4b) (a - 4b))`
    
     `= (a^2 + 16b^2 - (a^2 - 8ab + 16b^2))/((a + 4b) (a - 4b))`
    
     `= (a^2 + 16b^2 - a^2 + 8ab - 16b^2)/(a^2 - (4b)^2`
    
     `= (8ab)/(a^2 - 16b^2)`
    
        উত্তর: `(8ab)/(a^2 - 16b^2)`
    
       
      ঙ. `1/(x - y) - (x^2 - xy + y^2)/(x^3 + y^3)`
    
      `= ((x^3 + y^3) - (x - y) (x^2 - xy + y^2))/((x - y) (x^3 + y^3))`
    
      `= (x^3 + y^3 - (x^3 - x^2y + xy^2 - x^2y + xy^2 - y^3))/((x - y)(x^3 + y^3))`
    
      `= (x^3 + y^3 - x^3 + x^2y - xy^2 + x^2y - xy^2 + y^3)/((x - y)(x^3 + y^3))`
    
      `= (2x^2y - 2xy^2 + 2y^3)/((x - y)(x^3 + y^3))`
    
      `= (2y(x^2 - xy + y^2))/((x - y)(x + y)(x^2 - xy + y^2))`
    
      `= (2y)/(x^2 - y^2)`
    
       উত্তর :`(2y)/(x^2 - y^2)`






    1. Report
Copyright © 2025. Powered by Intellect Software Ltd